PERKEMBANGAN REGULASI MENGENAI BENEFICIAL OWNERSHIP DI INDONESIA BAGI KORPORASI DALAM BISNIS DAN PENCEGAHAN TINDAK PIDANA - Pradhana, Angga Pramodya; Chairani, Meirza Aulia; Yitawati, Krista (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2025)
This study analyzes the evolution of Beneficial Ownership regulations in Indonesia, focusing on their crucial role in corporate governance and the prevention of financial crimes, particularly Money Laundering and Terrorism Offenses. This study traces the legal framework from its basic instrument, namely Presidential Regulation No. 13 of 2018, to the significant strengthening marked by the issuance of Regulation of the Minister of Law and Human Rights No. 2 of 2025. The problems raised in this paper are (1) What is the role of beneficial ownership for corporations in Indonesian business? and (2) How can money laundering and terrorism financing be prevented in beneficial ownership for corporations? The type of research used is legal-normative, which focuses on the study of legislation and legal literature related to beneficial ownership in Indonesia. The analysis was conducted using a legislative and conceptual approach by understanding the legal framework, effectiveness, and challenges of implementing regulations in corporate practice. The results of the study show that (1) Beneficial Ownership plays a central role in increasing corporate transparency and accountability; (2) Prevention can be done with clear regulations and the implementation of beneficial ownership transparency, even though regulations have made significant progress, compliance and supervision challenges remain major obstacles. Therefore, increasing corporate awareness and capacity is essential so that the principle of beneficial ownership can effectively support the prevention of corporate crime and the creation of a transparent and accountable business environment in Indonesia. Keywords: Beneficial Ownership, Corporations, Money Laundering, Terrorism Offenses